Effect of Using Problem Solving Technique of 5Es Instructional Model on Student’ Learning at Secondary Level: An Analysis - Hassan, Sumaira; Zafar, Jam Muhammad; Ullah, Naeem (Pakistan Journal of Humanities and Social Sciences, 2024)
The study aimed to analyze,” Effect of Using Problem Solving Technique 5Es Instructional Model on Student’ Learning at Secondary Level”. The descriptive part was based on data collected through the questionnaire and the interview protocol from head teachers, teachers and students of class 10th. The experimental part was based on data collected through pre-test and post-test for 9th class students. The (QUAN-QUAL) method was executed and the explanatory sequential method was used. Four 4 Head teachers,16 English Teachers and 400 students200 girls and 200 boys studying in government schools in tehsil and district R.Y. Khan. The stratified sampling technique was implemented. The desired data was collected from Tehsil Rahim Yar Khan. The sample, sampling and sample size of the study was comprised; 4 secondary school head teachers with the same ratio of male and female; 16 secondary school English teachers with the same ratio of male and female; 400 students of secondary classes with the same ratio of male and female. The study found that majority (55%) of respondents agreed that they were interested in using problem solving technique in teaching of English. Mean value 2.94 shows a central tendency towards neutrality with a slight inclination towards agreement, indicating a moderate recognition of the role of interest in learning among respondents. The standard deviation 1.034 indicates moderate variability in responses suggesting that while there was some consensus; opinions on the influence of interest on learning still vary among the respondents. On the basis of these findings researcher presented some recommendations.